Android-based KKO Dictionary as a Tool in Formulating Indicators and Learning Objectives - Koro, Maxsel; Sampe, Markus; Un Lala, Sofia G; Ndolu, Sumardi W; Bessie, Marfelano (Universitas Pendidikan Ganesha, 2023)
Technology, which is developing rapidly at this time is a way out to overcome various problems in all aspects of life, one of which is the world of education. Formulating learning objectives based on basic competencies and indicators, guided by the use of operational verbs (KKO), can improve the quality of learning to the maximum. The main problem faced by teachers in developing indicators and learning objectives is determining KKO that are relevant to the level of each domain, of which the KKO spread across cyberspace are numerous and varied. For this reason, this research focuses on developing an operational verb dictionary (KKO) application which aims to help teachers when designing and developing learning tools, especially in formulating learning objectives. The subjects of this research were 12 teachers at SDI Lasiana, Kupang City. The resulting product will be tested for validity, practicality, and effectiveness when implemented by teachers when designing learning tools. The method used is research and development with a development model ADDIE. Validation results from experts show a feasibility level of 92% from material experts and 91.25% from media experts. If qualified it has a very worthy category. The results of the field trial showed that teachers felt interested and helped by the presence of the KKO dictionary application in preparing learning designs with maximum quality with an assessment score of 86.37% which can be interpreted as meaning that the product is very suitable for teachers to use in developing indicators and learning objectives effectively and efficiently.